Students’ Needs Analysis for the Development of Electronic Descriptive Reading Materials for Hotel Accommodation Program in VHS - Anisa Rhahima; Rita Inderawati; Eryansyah Eryansyah (Makassar State University, 2021)
Abstract. In this 21st century, students who are millennials are very accustomed to using electronic media in their daily lives, therefore electronic media, such as; smartphones, laptops, computers, and many others, have taken a central role in students' daily learning activities. This study aimed to obtain information about the needs of Vocational High School students in the field of reading English based on the use of media electronic learning. This study was qualitative and quantitative study in learning materials. In order to collect data for this study, questionnaires and semi-structured interviews were used. The questionnaires were distributed to 33 tenth grade students from SMKN 3 Palembang's hotel accommodation study program. The semi-structured interview was conducted with the tenth Grade-English teacher. The results showed that: 1) most of the students feel motivated when learning use the media electronic, 2) the specific aspects related to the hospitality sector that need to be combined into English reading text materials are descriptions of the jobs they will do later after graduating from the school so that they can increase their knowledge and expertise by their majors. The results of this study concluded that hotel accommodation students need electronic descriptive reading materials in learning activities. Therefore, this study is also used as the preliminary study in developing the electronic descriptive reading materials for hotel accommodation program of VHS.Keywords: Needs Analysis, Hotel Accommodation, Electronic Learning, Descriptive Text, and VHS.